Corrosion behaviour of microarc-oxidised magnesium alloy in Earle's balanced salt solution. Issue 1 (4th January 2017) - Zhang, Junqing; Zhang, Lei; Wilke, Benjamin M.; Li, Weiping; Ning, Chengyun; Chowdhury, Tonoy
Abstract : Microarc oxidation (MAO) coating is effective in improving the corrosion resistance of magnesium (Mg) alloys in a simulated body fluid. MAO coatings were deposited on AZ31 magnesium alloy at different pulse frequencies. Samples were immersed in Earle's balanced salt solution (EBSS) up to 21 d. Scanning electron microscopy, potentiodynamic polarisation testing, electrochemical impedance spectroscopy and X-ray diffraction (XRD) were performed to evaluate the corrosion behaviour of MAO coatings in EBSS compared to that of the uncoated AZ31. MAO-coated samples demonstrated improved corrosion resistance compared to the bare AZ31 throughout the corrosion period, indicating that MAO coating exhibited good corrosion protection of AZ31 in EBSS. Given the same immersion time, MAO-coated samples showed decreased corrosion current density and increased electrochemical impedance with increasing pulse frequency. The coating produced at 3000 Hz exhibited the best corrosion resistance compared to the ones produced at 300, 500 and 1000 Hz due to its uniform and dense structure. The XRD analysis showed that the corrosion products presented on the surface of the MAO-coated samples after immersion into the EBSS for 21 d were primarily composed of magnesium hydroxide, quintinite and hydroxyapatite. The corrosion mechanism of the MAO-coated AZ31 samples in EBSS is also discussed.